Energy Management Strategies for Extended-Range Electric Vehicles with Real Driving Emission Constraints - Hualong Xu; Yang Chen; Li Zhang; Guoliang Chen; Jinlin Han; Qing Zhang; Chaokai Li (Applied Sciences)
Fuel economy has long been the core control objective in the energy management strategies of extended-range electric vehicles (EREVs), but little research has considered real driving emissions. In this paper, the real driving emissions of an EREV are investigated, and the abnormal pollutant emissions caused by engine start–stop events are clarified. Accordingly, an interpolated-startup-corrected method is proposed to construct real driving emission models. Next, an optimization problem is constituted with real driving emissions as the constraints and fuel consumption as the objective. The optimization problem is solved using a dynamic programming (DP) algorithm embodying the interpolated-startup-corrected emission models, and the start–stop reduction strategies and condition migration strategies are derived. Compared to the strategy without the emission constraints, the CO and NOx emissions under the no-start–stop strategy are cut down by about 70%; the PN emissions are even orders of magnitude lower. Meanwhile, the condition migration strategy can compromise the fuel economy and pollutant emissions by adjusting the engine operating points, thus possibly limiting pollutant emissions beyond the start–stop reduction strategy.